Pengaruh Food Bar Berbasis Daun Katuk dan Daun Torbangun pada Profil Toksisitas Tikus Putih: The Effect of Food Bars Made from Katuk Leaf and Torbangun Leaf on the Toxicity Profile of White Rats - Baskara, Shelfia Chakarita; Nasrulloh, Nanang; Marjan, Avliya Quratul (Amerta Nutrition, 2024)
Background: Various herbal plants that grow in Indonesia, such as katuk leaves and torbangun leaves, are known to have many health benefits. These two plants contain important compounds such as vitamins, minerals and antioxidants which are beneficial for human health. Based on previous research, katuk leaves and torbangun leaves have been proven to increase breast milk production. However, studies regarding the benefits and potential toxicity of using these two herbal plants in experimental animals are still very limited. Therefore, this study was conducted to comprehensively evaluate and identify the toxicity profile observed in white rats after the administration of herbal supplements based on katuk leaves and torbangun leaves. This information is important to assess the safety of using these herbal preparations. Objectives: This study aimed to determine the level of safety and identify symptoms of toxicity in food bars containing katuk and torbangun leaf flour in male Wistar white rats. Methods: This study used a quantitative method with a true experimental design. The study samples consisted of 32 white mice divided into two groups. The rats were given food bars with katuk and torbangun leaf flour with doses ranging from 1.75 mg/kgBW to 17.5 mg/kgBW. Observations were made for 14 days regarding symptoms of toxicity, such as skin and fur changes, seizures, tremors, coma, and death. The statistical tests used were the normality test, homogeneity test, and hypothesis testing (ANOVA). Results: The results of the study showed that administering a food bar with katuk and torbangun leaf flour did not induce symptoms of toxicity in white rats. There was no significant difference in the mean body weight of mice between the two groups (p-value=0.109; p-value>0.05). Conclusions: Food bars with katuk and torbangun leaf flour did not have toxic properties and is safe to consume. Symptoms of toxicity were not evident in white mice given the food bar.